College Students Expectation Toward Tutor in Distance Education - Puspitasari, Susy; Chandrawati, Titi; Andriyani, Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Teacher performance will affect students' endurance, motivation, and spirit during learning. Someone's competence to become a teacher/Tutor is no longer enough by only mastering teaching materials, especially for tutors whose role is more as a facilitator. The purpose of this research is to find out the expectations of college students toward tutors in distance education. This research is qualitative by using a survey method. The aspect measured used an instrument of the Likert scale and then analyzed by using descriptive statistics. Key findings highlight that students recognize the importance of tutors' skills and appreciate the benefits of guided tutorials. There is a notable expectation among students for tutors and the Universitas Terbuka (UT) units to collaborate effectively to enhance tutorial services, which are integral to the learning structure in distance education. The results indicate a positive correlation between the tutors' abilities and the provision of efficient and effective learning support. Students' understanding of tutors' skills, their perception of the benefits of guided tutorials, and their internal consistency in evaluating tutor performance during tutorials are collectively rated as 'good'. This reflects the tutors' successful efforts in assisting students to become independent learners who are self-motivated and actively engaged in the learning process. The study underscores the need for focused tutor training programs aimed at developing competencies that align with students' expectations and the demands of distance education.